The determinants of product-specific rules of origin: An econometric analysis in the regional comprehensive economic partnership - Pramila Crivelli; Stefano Inama; Jeremy Marand (Asian Development Bank (ADB), 2024)
Rules of origin differ among overlapping free trade agreements, raising firm compliance costs, discouraging utilization of trade preferences, and hindering regional value chains. Using a unique dataset comparing the restrictiveness of product-specific rules of origin (PSRO) between the Regional Comprehensive Economic Partnership (RCEP) and other free trade agreements in Asia based on manufacturing requirements, this study aims to identify the factors explaining the stringency of RCEP PSROs. The econometric analysis based on maximum-likelihood models shows that economic sectors and political economy determinants and negotiating capacities significantly influence PSRO stringency under the RCEP. In particular, restrictiveness scores we develop show that (i) products for which developing RCEP members exhibit a strong revealed comparative advantage face stricter PSROs, and (ii) the degree of sophistication of the production process is positively related to PSRO leniency. This casts doubt on the potential for RCEP to provide a viable solution to the existing "noodle bowl" of rules of origin in Asia and reduce firms' costs of compliance in developing economies. It also demonstrates the need to strengthen aid for trade in policy and negotiations in developing Asia.
Keywords: F13; F15; 330; international trade agreements; product-specific rules of origin; market access; RCEP; regional integration; political economy